Analisis Dan Perancangan Sistem Informasi Manajemen Anggaran Pada Dinas Pendidikan Provinsi Jambi - Irawan, Asdi; Devitra, Joni (Jurnal Manajemen Sistem Informasi, 2020)
Every organization or plan needs to create an information system in order to support all activities so that the information generated can be carried out quickly and accurately. One of the information needed is information about the budget owned by an organization or authority. The issue of budget extraction in every expenditure, government expenditure becomes an important factor to stimulate a budget that adheres to the principles of budget savings, efficient and effective. The Jambi Provincial Education Office is a Regional Apparatus Organization (OPD) within the Jambi Provincial Government Environment which is responsible for education by the Governor through the Jambi Provincial Regional Secretary. Therefore the Thesis Report with the title "Analysis and Design of Budget Management Information Systems at the Jambi Provincial Education Office". The purpose of this thesis discussion is in the preparation and reporting of budgets that contain the principles needed between approval and accountability of other budgets, budget coordination, budgetary budgets, budget efficiency and budgets. When carrying out a complicated budget preparation and reporting process, it turns out that in its application the system uses manuals and there is no system that is integrated with the process of making and making budget reports to be better and supporting activities and cost plans that are not in accordance with predetermined targets.